Density - Velocity Relationship and Prediction of Lithology Variation Using Physical Analysis in Kf-4 Well of The Kifl Oil Field, Yamama Formation, South of Iraq - Alobaidy, Abdulaziz R.; Al-Banna, Ahmed S. (Iraqi Journal of Science, 2021)
The density-velocity relation is an important tool used to predict one of these two parameters from the other. A new empirical density –velocity equation was derived in Kf-4 well at Kifl Oil Field, south of Iraq. The density was derived from Gardner equation and the results obtained were compared with the density log (ROHB) in Kl-4 well. The petrophysical analysis was used to predict the variations in lithology of Yamama Formation depending on the well logs data, such as density, gamma, and neutron logs. The physical analysis of rocks depended on the density, Vp, and Vs values to estimate the elastic parameters, i.e. acoustic impedance (AI) and Vp/Vs ratio, to predict the lithology and hydrocarbon indicators. According to the results of physical properties, Yamama Formation is divided into five units in Kf-4 well at Kifl Oil Field. The lithology of Yamama Formation was found to consist of limestone, dolomite, shale, and anhydrite rocks.